Pengembangan Inovasi Pengolahan Produk, Pelatihan dan Pendampingan Basic Income Statement pada Kelompok Usaha Pemindangan Ikan “Rujuk Kembali” di Dusun Selindungan Desa Pelangan Kecamatan Sekotong - Abjadi, Khalid; Asmony, Thatok; Purwadinata, Subhan; Pituringsih, Endar; Syukur, Abdul; Sari, Khopipah Wandan (Universitas Mataram, 2025)
This training and mentoring program targeted the Fish Smoking Business Group in Selindungan Hamlet, Pelangan Village, Sekotong District, West Lombok Regency. It aimed to enhance participants' knowledge and skills in fish product innovation and basic income statement preparation. The materials covered included innovative fish processing techniques and simple financial recording to help members calculate profits and prepare financial reports. The results indicate improved understanding among group members in developing more competitive fish products and preparing basic financial statements. The program is expected to foster entrepreneurial independence and improve the welfare of the business group members.